Comparative study of remote and face-to-face teaching of mechanical ventilation: a website proposal (International Seven Journal of Multidisciplinary, 2023)
The Covid-19 pandemic has challenged health professionals who work on the front lines of this serious health situation, especially in terms of the ability to perform the Mechanical Ventilation (MV) technique in patients who need respiratory support. The handling and technique of a mechanical ventilator is one of the major concerns of these professionals in the Emergency Room (ER), Intensive Care Unit (ICU) and in urgency and emergency services. After graduation, several health professionals assume leadership positions in teams that work in areas of emergency care without having specific qualifications for MV, a situation that generates difficulties, anguish, stress and care deficiencies. In addition, there is a great demand for qualified professionals in times of pandemic and social distance, and thus there was an expansion of training and remote and/or online study activities using Digital Technologies tools connected to the internet. Thus, this study aimed to comparatively evaluate face-to-face and remote teaching, in the handling of MV for health professionals who are on the front lines of the Covid-19 pandemic. For this purpose, an Educational Product (EP) was developed in the form of a website, questionnaires and video class with theoretical content and practical demonstrations of the techniques. The material was developed for health professionals and used to assess the quality of face-to-face and remote teaching with participants who answered knowledge survey questionnaires on the subject before training, and also a final questionnaire after attending the class. In the pre-test, it was possible to verify that the average presented in the face-to-face group was 3.00, while in the remote teaching it was 4.62, considering a disparity in the data. This result shows that in an average above 4, half of the participants got 4 questions right. In the post-test, there is a parity of means with values of 3.10 for the face-to-face group and 3.24 for the remote group. In turn, it was possible to verify that in the remote teaching post-test there was a decrease in correct answers. These differences evidenced in the remote group for the pre-test and the post-test had a significance of 0.030. Conclusion: Through the present research, a gap in pre-existing knowledge was observed in some professionals who already worked directly with the subject before training. After remote teaching, a significant number of participating health professionals correctly answered the post-test questions. Although remote teaching participants showed lower performance in the post-test when compared to the pre-test, this group got more questions right than professionals who received the training in person. Remote teaching can be an immediate response to demands with the Basic Mechanical Ventilation theme, especially in periods of social isolation. However, future studies will still be necessary to affirm if there is an improvement in distance learning when compared to the face-to-face methodology.